(untitled) (Bangladesh Journal of Medical Science, 2024)
Background and objective Mizajis one of the basic concepts of the Unani system of medicine upon which diagnosis and line of treatment of disease are based. According to Unani medicine, each person has uniquely Mizāj recognized by physiological, psychological, and therapeutic features. Mizāj plays an essential role in the diagnosis and treatment of disease as well. Unani scholars describe several parameters for Mizaj assessment. Some relate to the structure, and others to the functions. Due to the lack of scientific validation, no standard method or tool is available to determineMizāj in conducting research and in medical practice. The objective of the present study is to develop a practical tool in the form of a questionnaire for the determination of individual Mizāj on the human body, so based on a thorough literature scan about Mizaj, items of the questionnaire were framed, and the inter-rater judgment analysis was carried out to validate the items. Methods Survey of available literature, especially classical Unani books, journals, theses, dissertations, etc. Results The result was evolved based on the questionnaire for assessing Mizāj-i-insani. The questionnaire was evaluated by ten experts in Unani medicine, and their marks were set; the data analysis showed significant agreement in selecting one of the items in respect of the determination of Mizāj-i-insani. Conclusion: The questionnaire formulated based on available literature in Unani medicine consists of items for which there was substantial agreement between the experts for item validation. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 429-437